Evaluation of Anxiety and Experience of patients presented with Maxillofacial Trauma in Nishtar Institute of Dentistry - Tauseef Zahra, Zehra Jawa, Tehzeeb Zahra, Asif Nazeer, Hassan Raza, Usma Batool (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the anxiety in patients of maxillofacial trauma using HAM-A scale presenting in emergency department and compare it with elective maxillofacial surgery patients Study design: Analytical cross sectional study. Place and duration of study: Study was conducted from May 2021 to Apr 2022 at Dental unit of Nishtar Institute of Dentistry. Methodology: 80 patients who met the inclusion criteria were included. Inclusion criteria was any patient aged between 12-80 years irrespective of gender who got isolated facial trauma, patients with no previous history of psychological disorder. Hamilton anxiety scale was used to make a proforma which was filled by on duty post graduate trainee. p-value of ≤0.05 was significant. Results: There were 61 males (76.2%) and 19(23.8%) females. Mean age of patients in group A (facial trauma) was 40.5±15.20 years and in group B (elective surgery) was 50.2±10.47 years. HAM-A score in group A was 25.15±9.74 (moderate to severe anxiety) and in group B it was 12.12±4.44 (mild anxiety) which was statistically significant. (p value 0.00). Conclusion: Maxillofacial injuries may pose a heavy impact psychological lives of patients and patients may suffer from anxiety and depression. A multidisciplinary team approach with surgeon and psychiatrist be included to reduce physical damage and psychological impact on patients. Keywords: Anxiety, depression, maxillofacial trauma